Pengaruh Dimensi Kualitas Pelayanan Terhadap Kepuasan Nasabah Koperasi Simpan Pinjam Lego-Lego Kalabahi Kabupaten Alor - Elia Maruli; Alvonso Fanisius Gorang; Sefnat Aristarkus Tang; Theresia L. L. Peny (Peneliti.net, 2022)
Customer satisfaction is the customer's perception that his expectations have been met, optimal results are obtained for each customer and the service of the Cooperative by taking into account the abilities of customers and their families, paying attention to customer needs so that the best continuity is between satisfaction and results. This study was conducted on 40 customers with the aim of this study being to determine the effect of physical evidence (tangible), reliability (reliability), assurance (assurance), responsiveness (responsiveness), empathy (empathy) on customer satisfaction Lego Savings and Loans Cooperatives. Lego Kalabahi, Alor Regency. Collecting data using observation techniques, interviews, questionnaires, and documentation studies. Data analysis used t test (partial test) and F test (simultaneous test). The results of the study show that partially the variables consisting of variables (tangible, reliability, assurance, responsiveness and empathy) have a significant effect on customer satisfaction. Simultaneously the variables consisting of tangible, reliability, assurance, responsiveness and empathy together all variables have a significant effect on customer satisfaction of the Simapan Pinajm cooperative in the Kalabah Savings and Loan Cooperative, Teluk Mutiara District, Alor Regency